Are Anthelminthic Treatments of Captive Ruminants Necessary? - Liron Lahat; Juana M. Ortiz; Paolo Tizzani; Belén Ibáñez; Francisco Valera; Eulalia Moreno; Gerardo Espeso; Rocío Ruiz de Ybáñez (Veterinary Sciences, 2021)
Anthelmintics are frequently administered to animals to limit fecal egg elimination, so that wild animals in captive breeding programs are treated to maintain a proper health condition. This is effective from a health management perspective, but on the other hand, it could prevent captive animals from developing an effective immunity against parasites that they might encounter when reintroduced into their original geographic areas. The aim of this study was to describe the dynamics of parasite infections in captive Cuvier’s gazelles (Gazella cuvieri) not treated with anthelmintics for two years and to evaluate the factors related to their fecal egg shedding. Fifteen one-year-old males were enclosed together and captured monthly to collect feces directly from the rectum. Fecal egg counts were performed, and eggs were classified as strongylid-like, Nematodirus sp., or Trichuris sp. Fecal egg shedding for the three groups of parasites did not vary significantly over the duration of the study. Only precipitation affected the egg-shedding pattern of all parasites, while inbreeding was positively associated with the number of strongylid-like parasites. These findings suggest an equilibrium between hosts and parasites in absence of treatment during the study. The anthelmintic treatment as a systematic prophylaxis method in captive animals should be avoided and replaced by systematic coprological and clinical vigilance, as well as targeted treatment in the case of a significant rise of fecal egg counts.